DISCLOSURE OF INTANGIBLE ASSETS IN FINANCIAL STATEMENTS (American Journal of Business Management, Economics and Banking, 2025)
This article presents the procedure for disclosing information about intangible assets in the financial statements of enterprises, including the statement of financial position and the statement of financial performance. It also provides proposals and recommendations on the presentation of information regarding intangible assets in financial statements. Based on these proposals, enterprises are enabled to harmonize their financial reporting forms with international standards.